Intelligent assessment system robotic / Nurul Ain Hassim - Nurul Ain , Hassim (2005)
Intelligence is harder to define than knowledge. When researchers m the field of artificial intelligence talk about intelligence in technical systems, they usually use it to suggest that their software is more flexible, more readable, and easier to use than some other software. Early attempts were limited to only simple grading of assignment, but recent developments have started to focus on adaptive assessment. The assessment systems use adaptive approaches to support intelligent assessment and individualized learning. Various approaches have been used for this purposed and the field is still quite new. Keeping this in my mind, I decided to build the new intelligent assessment system which is adaptive and focusing in robotic domain. This intelligent assessment system is a stand alone system. This assessment system is integrated between three topics in robotic syllabus. There are speech synthesis, motion and vision. The users that are allowed to use this system are either the expert or novice user. The aim of this project is to provide efficient intelligent mediated learning for the student and to provide helps based on the student's categorized either beginner, intermediate or advance student. I believe it's important to build a strong foundation and linking for robotics in order to ensure that will be ready to face new and often exciting challenges that they will encounter in their studies. To love something, we have to like something. And to like something, we have to know something. The Intelligent Assessment System is thus proposed to overcome any shortcomings that other systems in other fields have. The build system will have and attractive user interface to make the assessment process more efficient. This system will be built using Visual Basic 6 as a programming tool. The methodology that will be using through out this system is waterfall model. And to help lost or inexperienced computer users, the system will be built to cater the needs and help students along the way. In order to build a comprehensive system, related information is gathered from the books, internet and other learning material. It is hoped that the development of this intelligent assessment system will further assist students to better understanding in robotic domain.